The EATMOT Project: Preliminary Results of the study about motivations for food choices in 16 countries - Guiné, Raquel (2019)
Eating is not only determined by physiology, but also by many other factors that interact in a complex way to shape individual eating habits. Hence, the aim of this project is to undertake a study about the different psychic and social motivations that determine people’s eating patterns, either in relation to their choices or eating habits. To do this, factors linked to food choices will be evaluated in the following main areas: health motivations; economic factors; emotional aspects; cultural influences; marketing and commercials or environmental concerns. The study is based on a questionnaire that was prepared purposely for the project, and therefore adequate to evaluate the aspects that determine the objectives highlighted. The study is coordinated by the principal researcher Raquel Guiné from CI&DETS Research Centre and the range is multinational, including different countries so as to gather information on a trans-frontier scale. The countries involved are: Argentina, Brazil, Croatia, Egypt, Greece, Hungary, Italy, Latvia, Lithuania, Netherlands, Poland, Portugal (Coordinator), Serbia, Slovenia, Romania and United States of America. This particular study investigated the influence of sociodemographic factors on the six types of eating motivations previously referred. This is a longitudinal observational study carried out on a non-probabilistic sample with 11960 participants residing in the 16 countries afore mentioned. Analysis of the data was performed using t-test for independent samples or ANOVA with Post-Hoc Tukey HSD. Neural network models were also created, to determine the relative influence of each input on each output variable. The results showed that factors such as age, marital status, country, living environment, level of education or professional area significantly influenced all of the studied types of eating motivations. The modelling through neural networks indicated a considerable variability in the food choices, but still it was possible to identify some trends, like for example that the strongest positive factor determining health motivations was age, while for emotional motivations was living environment, and for economic & availability motivations was gender. On the other hand, country revealed a high positive influence for the social & cultural as well as for environmental & political and also for marketing & commercial motivations.